2011
DOI: 10.1007/s11661-011-0736-6
|View full text |Cite
|
Sign up to set email alerts
|

Cracking Phenomenon Occurring in Bi-S–Based Free-Machining Steel Wire Rods During Hot Rolling

Abstract: In this study, cracks or scabs formed during hot rolling of Bi-S-based free-machining steel wire rods were analyzed, and their formation mechanisms were clarified in relation with microstructure. Detailed microstructural analyses of large-diameter rods showed that the rod having low carbon content was cracked, whereas the rod having higher carbon content was not, because oxides formed during hot rolling were penetrated into the relatively soft surface, thereby leading to the surface cracking. While the crack-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…In general, an excess amount of MA constituents inside GB or DUB readily deteriorates the toughness of high-strength steels, because some applied load is locally concentrated at these constituents and thus should be controlled adequately in strength and toughness considerations. [12,13] It has been found that the MA constituent is formed through the process controlled by carbon diffusion when some part of carbon-enriched austenite transformed to martensite, and the size and amount depend on various parameters such as the chemical composition, cooling rate, FCT, etc. [2,12,13] …”
Section: A Cct Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, an excess amount of MA constituents inside GB or DUB readily deteriorates the toughness of high-strength steels, because some applied load is locally concentrated at these constituents and thus should be controlled adequately in strength and toughness considerations. [12,13] It has been found that the MA constituent is formed through the process controlled by carbon diffusion when some part of carbon-enriched austenite transformed to martensite, and the size and amount depend on various parameters such as the chemical composition, cooling rate, FCT, etc. [2,12,13] …”
Section: A Cct Characteristicsmentioning
confidence: 99%
“…[12,13] It has been found that the MA constituent is formed through the process controlled by carbon diffusion when some part of carbon-enriched austenite transformed to martensite, and the size and amount depend on various parameters such as the chemical composition, cooling rate, FCT, etc. [2,12,13] …”
Section: A Cct Characteristicsmentioning
confidence: 99%
“…Studies have shown that morphology of martensite particles plays an important role in the strength and ductility of the dual phase steels [2][3][4][5][6]. However, most of the research work has been focused on comparison of martensite morphology produced by some variations of two basic heat treatments, the quenching (or step quenching) process from austenite region, or the intercritical annealing [3,[5][6][7][8][9][10][11][12]. Martensite particles in the first treatment tend to have the same crystallographic orientation as the surrounding ferrite matrix [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] They have attracted considerable attention in the automotive industry in recent years due to their superior formability and high strength to weight ratio. [8][9][10][11][12][13][14] Dual-phase steels are processed to a composite microstructure with interesting mechanical properties such as continuous yielding, low yield stress to tensile strength ratios, high initial work-hardening rate, high strength, and good ductility. This microstructure is comprised primarily of a relatively soft ferrite matrix and hard martensite particles, although it may contain other constituents (retained austenite, bainite, and pearlite).…”
Section: Introductionmentioning
confidence: 99%
“…[21] It seems that different failure mechanisms (void nucleation and growth) of particular DP steels may be related to their chemical compositions, history of heat treatment, and differences of their final microstructure. [4,[6][7][8][9]11,12,[16][17][18][19][20][22][23][24][25][26][27][28][29][30][31] Significant plastic deformation of martensite occurs when its strength is reduced either by carbon content or by tempering. With respect to void nucleation, such as martensite cracking, Stevenson [30] reported that voids could be mainly nucleated by cracking of martensite islands.…”
Section: Introductionmentioning
confidence: 99%